Kesalahan Penggunaan Bahasa Indonesia dalam Ruang Publik (Media Luar Ruang) di Kota Baubau - Nazriani Nazriani; Arsad Arsad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2020)
The influence of foreign languages, especially English may erode Indonesian authority. Most people feel more confidence and smarter when using English. It is not wrong but contradict to the slogan echoed by the government,